1989
DOI: 10.1080/00150198908211286
|View full text |Cite
|
Sign up to set email alerts
|

X-ray studies of electrocaloric lead-scandium tantalate ordered solid solutions

Abstract: Precision x-ray studies. polarization and electrocaloric measurements have been made with PST-PSN solid solutions in the temperature range -180-+8O"C. The large electrocaloric effect AT = 1.0-1.7"C is due to both particular features of structure rearrangement at the 1-order phase transition in the materials and a high ion ordering in sublattice B of the perovskite structure ABO,.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 2 publications
(1 reference statement)
0
16
1
Order By: Relevance
“…The four bipolar plots show that the ferroelectric loop at 280 K became a double loop 41 over a limited range of temperatures above T C , evidencing the field-driven transition in PST (ref. 36). However, we will use our unipolar plots in what follows because the field hysteresis is smaller.…”
Section: Resultsmentioning
confidence: 99%
“…The four bipolar plots show that the ferroelectric loop at 280 K became a double loop 41 over a limited range of temperatures above T C , evidencing the field-driven transition in PST (ref. 36). However, we will use our unipolar plots in what follows because the field hysteresis is smaller.…”
Section: Resultsmentioning
confidence: 99%
“…3) Following his study, many ceramic materials were studied such as SrTiO 3 4) and KTaO 3 ,5) the antiferroelectric Pb(Zr,Ti)O 3 , 6) and the ferroelectrics Roshelle salt, 3) KH 2 PO 4 , 7) BaTiO 3 , 8) TGS, 9) Pb(Zr,Ti)O 3 , 6,10) Pb(Sc,Ta)O 3 , [11][12][13][14] and Pb(Mg,Nb)O 3 -PbTiO 3 . [15][16][17] However, these temperature changes were smaller than 2.5 K. 18) In 2006, Mischenko et al suggested that a much larger ΔT appears near the para=ferro critical point.…”
Section: Introductionmentioning
confidence: 99%
“…[229][230][231] [232,233] The "cationordered" phase where the Sc and Ta ions are each arranged in alternating B-site positions throughout the lattice behaves as an ordinary FE with a first-order paraelectric-FE phase transition at ≈295 K. [234] On the other hand, the "cation-disordered" phase can behave as a relaxor FE. [106,235,236] The degree of ordering in PST is defined by the long-range order parameter Ω given by Ω = 2n − 1 where n is the occupation number of the Sc atoms in the B sites. The critical temperature T C where the dielectric constant is at a maximum in PST is dependent on the long-range order parameter with T C = 311 K for Ω = 0 to T C = 323 K for Ω = 0.94.…”
Section: Pst-based Ceramics and Thin Filmsmentioning
confidence: 99%
“…Lead scandium niobate, Pb(Sc 0.5 Nb 0.5 )O 3 (PSN) also has a A(B x B′ 1−x )O 3 type complex perovskite structure (similar to PST) where the degree of ordering between Sc 3+ and Nb 4+ ions in B sites is determined by the thermal prehistory of the material. [106,233,238] When processed in a manner that does not suppress lead vacancies, they exhibit normal relaxor FE behavior. However, if stoichiometry is controlled, disordered PSN transforms spontaneously from a relaxor into a normal FE upon cooling.…”
Section: Psn-based Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation